Rancang Bangun Sistem Deteksi Gerakan Mata untuk Pemilihan Enam Menu Display menggunakan Circular Hough Transform berdasarkan Facial Landmark berbasis NVIDIA Jetson Nano - Imam Faris; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Person with hand disabilities who often have difficulties in carrying out daily activities as normal human. One of the cases for people with hand disabilities is difficulty when want to turn on electronic devices such as televisions, lights and other devices so required the help of nurses. The solution offered is to create a tool for people with disabilities to select six screen display menus using the circular hough transform method in making menu selections without have to direct contact with the device. This system works by detecting the movement of circles on the iris of the eye, namely movement to the oblique left, up, oblique right, left, down, and movement to the right. The output of the system is that the user can choose six smart assistant menu displays and voice output. The center point of the iris will be processed by computer to be used as a cursor that can execute commands from the user in making menu selections, and blinking for 0-3 seconds will command the menu to be activated. The average value of the accuracy level of the whole system on the distance variation 30, 40 and 50 cm eye movement detection system is 85.18% with a computation time of 0.1816 seconds. The system can be used to help people with disabilities and lighten the work of nurses in understanding the activities required by people with hand disabilities.